2020
DOI: 10.3390/ijms21155456
|View full text |Cite
|
Sign up to set email alerts
|

Immune-Checkpoint Blockade Therapy in Lymphoma

Abstract: Tumor cells use immune-checkpoint pathways to evade the host immune system and suppress immune cell function. These cells express programmed cell-death protein 1 ligand 1 (PD-L1)/PD-L2, which bind to the programmed cell-death protein 1 (PD-1) present on cytotoxic T cells, trigger inhibitory signaling, and reduce cytotoxicity and T-cell exhaustion. Immune-checkpoint blockade can inhibit this signal and may serve as an effective therapeutic strategy in patients with solid tumors. Several trials have been conduct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
21
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 100 publications
0
21
0
Order By: Relevance
“…Immune checkpoint inhibitors, which enhance T-cell activation, have exhibited antitumor activity in preliminary studies within some lymphoma subtypes, principally classical Hodgkin lymphoma. [5][6][7][8] While the role of immune checkpoint proteins in the pathogenesis of DLBCL has not yet been fully elucidated, a recent meta-analysis indicated that high expression of programmed death-ligand 1 (PD-L1) was associated with poor prognosis in patients with DLBCL. 9 PD-L1 represents a potential therapeutic target in DLBCL; the anti-PD-L1 antibody durvalumab showed efficacy in patients with treatment-naïve DLBCL when administered in combination with R-CHOP.…”
Section: Resultsmentioning
confidence: 99%
“…Immune checkpoint inhibitors, which enhance T-cell activation, have exhibited antitumor activity in preliminary studies within some lymphoma subtypes, principally classical Hodgkin lymphoma. [5][6][7][8] While the role of immune checkpoint proteins in the pathogenesis of DLBCL has not yet been fully elucidated, a recent meta-analysis indicated that high expression of programmed death-ligand 1 (PD-L1) was associated with poor prognosis in patients with DLBCL. 9 PD-L1 represents a potential therapeutic target in DLBCL; the anti-PD-L1 antibody durvalumab showed efficacy in patients with treatment-naïve DLBCL when administered in combination with R-CHOP.…”
Section: Resultsmentioning
confidence: 99%
“…To discern the mechanism of action of ICIs, it is crucial to understand how the CTLA-4 and PD-1 ligands play a role in the immune response. CTLA-4 regulates T-cell proliferation early in an immune response, primarily in lymph nodes, whereas PD-1 suppresses T-cells later in an immune response, primarily in peripheral tissues (4). CTLA-4 works by indirectly diminishing signaling through its co-stimulatory receptor, CD28 (Figure 1).…”
Section: Mechanism Of Actionmentioning
confidence: 99%
“…Cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) binds to CD80 (B7-1) or CD86 (B7-2) and decreases activity of T cells by interrupting CD28-mediated co-stimulatory signaling. Aberrant overexpression of programmed death ligands 1 and 2 (PD-L1, PD-L2) or T-cell immunoglobulin and mucin domain 3 (TIM3) on malignant cells induce T-cell impairment, exhaustion, and apoptosis [ 64 , 65 , 66 ]. With the approval of several immune checkpoint inhibitors for the treatment of diverse solid cancers, it is now evident that the original proof-of-concept of inhibition of cancer-induced immunosuppression successfully translated into clinical practice.…”
Section: Immune Checkpoint Inhibitorsmentioning
confidence: 99%